24-h monitoring devices and nyctohemeral rhythms of intraocular pressure. (November 2016) - Aptel, Florent; Weinreb, Robert N.; Chiquet, Christophe; Mansouri, Kaweh
Abstract: Intraocular pressure (IOP) is not a fixed value and varies over both the short term and periods lasting several months or years. In particular, IOP is known to vary throughout the 24-h period of a day, defined as a nyctohemeral rhythm in humans. In clinical practice, it is crucial to evaluate the changes in IOP over 24 h in several situations, including the diagnosis of ocular hypertension and glaucoma (IOP is often higher at night) and to optimize the therapeutic management of glaucoma. Until recently, all evaluations of 24-h IOP rhythm were performed using repeated IOP measurements, requiring individuals to be awakened for nocturnal measurements. This method may be imperfect, because it is not physiologic and disturbs the sleep architecture, and also because it provides a limited number of time point measurements not sufficient to finely asses IOP changes. These limitations may have biased previous descriptions of physiological IOP rhythm. Recently, extraocular and intraocular devices integrating a pressure sensor for continuous IOP monitoring have been developed and are available for use in humans. The objective of this article is to present the contributions of these new 24-h monitoring devices for the study of the nyctohemeral rhythms. In healthy subjects and untreated glaucoma subjects, a nyctohemeral rhythm is consistently found and frequently characterized by a mean diurnal IOP lower than the mean nocturnal IOP, with a diurnal bathyphase – usually in the middle or at the end of the afternoon – and a nocturnal acrophase, usually in the middle or at the end of the night.